Prinsip Transparansi Layanan Perbankan di Aplikasi Jenius SMBC Indonesia Tbk Ditinjau dari Peraturan OJK - Nina Indah Febriana; Melani Ayu Anisak (Jimly School of Law and Government, 2024)
The research was motivated by the allegation that the principle of transparency was not applied to Jenius SMBC Indonesia Tbk's banking services, so it needs to be reviewed through OJK Regulation No. 17 of 2023 on the Implementation of Governance for Banks, OJK Regulation No. 21 of 2023 on Digital Services by Commercial Banks, and OJK Regulation No. 22 of 2023 on Consumer and Community Protection in the Financial Services Sector. The objectives of this study are: 1) Analysing the implementation of the principle of transparency of banking services at Jenius SMBC Indonesia Tbk, 2) Analysing the suitability of the implementation of the principle of transparency of banking services at Jenius SMBC Indonesia Tbk with the provisions of OJK Regulations. The research method used by the researcher is a field research method with a qualitative approach. The data collection procedures used in this study include observation, interviews, and documentation. Meanwhile, the data analysis technique uses several stages including data collection, data reduction, and data presentation, and ends with conclusion and verification. The results of this study show that the implementation of the principle of transparency of banking services at Jenius SMBC Indonesia Tbk in general has been running well, but not all users are willing to read and understand RIPLAY. On the other hand, nominal details are not mentioned on RIPLAY and the information on answers to questions about feesible fees is not displayed. The information system of Jenius SMBC Indonesia Tbk does not comply with the provisions of the principle of transparency, including the non-fulfilment of the provisions of Article 30 Paragraph (1) Letter a, which is related to the substance of RIPLAY and Article 32 Paragraph (1) OJK Regulation No. 22 of 2023 where the information on answers to questions about feesible fees is not clearly stated at RIPLAY.